2010
DOI: 10.1007/s11912-010-0139-7
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Cancer Risk: Recent Review and Evidence

Abstract: The prevalence of overweight and obesity is increasing worldwide, and the evidence base for a link between obesity and cancer is growing. In the United States, approximately 85,000 new cancer cases per year are related to obesity. Recent research has found that as the body mass index increases by 5 kg/m2, cancer mortality increases by 10%. Additionally, studies of patients who have had bariatric surgery for weight loss report reductions in cancer incidence and mortality, particularly for women. The goal of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
242
0
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(255 citation statements)
references
References 34 publications
4
242
0
9
Order By: Relevance
“…4,25 Several mechanisms have been proposed to explain how obesity increases HCC risk, with the primary underlying condition being NASH. 6 We have previously shown that extended feeding of the HF-HC-HSD alone results in NASH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,25 Several mechanisms have been proposed to explain how obesity increases HCC risk, with the primary underlying condition being NASH. 6 We have previously shown that extended feeding of the HF-HC-HSD alone results in NASH.…”
Section: Discussionmentioning
confidence: 99%
“…2 Recently large-scale epidemiological studies have pointed out that overweight and obese individuals possess substantial increase in cancer risk. 3,4 Although the obesity-associated increase in cancer risk is dependent on the type of cancer, the largest increase is seen for HCC. 5 Several mechanisms are proposed to explain how obesity increases HCC risk, including the prevalence of type II diabetes, Non Alcoholic Steato-Hepatitis (NASH), and cellular inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…These hormones are responsible for body cell growth and division; hence, contribute to the growth of cancer cells [19]. Obese menopausal women have been found to have higher percentage of circulating estrogen that is produced from adipose tissue.…”
Section: Obesity-cancer Connectionmentioning
confidence: 99%
“…Az alimentáris eredetű májkárosodásban csökkent metilpool felhívja a fi gyelmet az elhízás és a rák kialakulása közötti kapcsolatban a metilezettségi szint jelentőségére [45,46,47].…”
Section: Megbeszélésunclassified